2015
DOI: 10.1089/apc.2014.0293
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Patient Motivation to Adhere to Combination Antiretroviral Therapy in South Africa

Abstract: Taken as prescribed, that is, with high adherence, combination antiretroviral therapy (ART) has changed HIV infection and disease from being a sure predictor of death to a manageable chronic illness. Adherence, however, is difficult to achieve and maintain. The CAPRISA 058 study was conducted between 2007 and 2009 to test the efficacy of individualized motivational counselling to enhance ART adherence in South Africa. As part of the overall trial, a qualitative sub-study was conducted, including 30 individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Previous studies have shown that positive attitudes towards ART and the immediate effect of gaining strength upon taking ART facilitated patients’ adherence and further reinforced their desire to live long and healthy (Kumarasamy et al, 2005; Loggerenberg et al, 2015; Penn, Watermeyer, & Evans, 2011; Reda & Biadgilign, 2012; Watt et al, 2009). We found that other motivators such as disease control, preventing infections or TB was moderately ranked and similarly valued among those with and without current partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that positive attitudes towards ART and the immediate effect of gaining strength upon taking ART facilitated patients’ adherence and further reinforced their desire to live long and healthy (Kumarasamy et al, 2005; Loggerenberg et al, 2015; Penn, Watermeyer, & Evans, 2011; Reda & Biadgilign, 2012; Watt et al, 2009). We found that other motivators such as disease control, preventing infections or TB was moderately ranked and similarly valued among those with and without current partners.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing or counseling among PLWH has been used as an important tool to emphasize individual health benefits of ART and to encourage comprehensive HIV prevention (Hill & Kavookjian, 2012; Safren et al, 2001, 2009). Qualitative studies have shown that individuals who perceive the benefits of ART as “life-giving” and providing better overall health tend to have higher adherence (Kumarasamy et al, 2005; Loggerenberg et al, 2015). Partners also play an important role in determining ART initiation or retention in care but such influence may differ by partner’s HIV status (Morton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They adhered to the treatment and were aware of the consequencies of failure to adhere to their HIV treatment. Participants reported proper adherence despite the challenges as reported in other studies (van Loggerenberg et al, 2015). They were also informed that this wasn't HIV treatment but rather minimised the effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar knowledge in Somalia remain abstract because of the civil strife and unrest that has brought continuos fragility in the country, particularly in Mogadishu region. Despite the drafting of the national HIV strategy, Somalia still faces challenges of low coverage of HIV services with low capacity for monitoring and evaluation, poor supply of food and medicines in addition to the insecurity (UNAIDS, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the shift to the so-called "post-AIDS era" (Dowsett & McInnes, 1996) -an allusion to HIV becoming a chronic condition thanks to the availability of ARVs and the development of more effective diagnostic tools for monitoring HIV, such as the viral load test -the topic of HIV biomarkers and their relation to a person's everyday experience with HIV has proven to be of considerable academic interest (see Persson, 2004;Persson & Newman, 2006;Sangaramoorthy, 2012;Newman et al, 2015;van Loggerenberg et al, 2015). This article seeks to build on this research by interrogating the popular technology of an advice column as a platform for self-help and undertaking health.…”
Section: Introductionmentioning
confidence: 99%